INTEGRATED EMULSION PAINTS DERIVED FROM THREE POLYVINYL ACETATE (PVA) GROUNDNUT OIL - Usman, Y. M.; Ndahi, J. A.; Modibbo, U. U.; Baka, E. F.; Agabus, D.; Abdullahi, Z. A.; Liman, I. A. (FUDMA Journal of Sciences, 2024)
A modified paint was produced in this research to supplement and substituteproducts by tender small-scale private paint factories, in an era of increasing demand of paints by the nation’s alarmingly growing building technology. The research was aimed at the formulation of an emulsion paint with the aid of polyvinyl acetate mixed with Groundnut oil as a binder by reducing volatile organic compounds and to determine the major physical parameters such as drying time, period of elongation, density, refractive index, adhesion, pH, and chemical resistance. The result obtained showed increase of dry to hard from Pure PVA paint (90.23 minutes) followed by Gombe PVA paint (105.5 minutes) to Taraba PVA paint (110.00 minutes). The drying time of the paint samples was in this order Taraba PVA paint (80.0 min) > Gombe PVA paint (75.5 min) > Pure PVA paint (75.23 min). The dry to touch was in the decreasing order: Taraba PVA paint (56.2 min) > Gombe PVA paint (53.4 min) > Pure PVA oil (49.15 min). The density (g/cm3) showed that Gombe PVA paint (1.16) > Pure PVA paint (1.30) > Taraba PVA paint (1.10). The solubility test for both Taraba PVA Groundnut paint and Gombe PVA Groundnut derived paint are practically insoluble in water, while Pure PVA derive paint dissolved in water instantly. All the three formulated paints passed the resistance blistering and flexibility tests. FTIR showed the following functional groups Hydroxyl, Amines, Carboxylic acids, Alkylhallides, Ketones and Aldehydes at specific wavelength are present in paints that serves as...